Novel handover scheme for indoor VLC systems. Issue 8 (17th February 2021) - Younus, Safwan Hafeedh; Al‐Hameed, Aubida A.; Hussein, Ahmed Taha
Abstract: Managing mobility in visible light communication systems is one of the main encounters that requires to be tackled. In this paper, we propose subcarrier multiplexing tones as control signals for handover in visible light communication systems. These control tone signals are unmodulated signals, and each light unit is given a unique unmodulated control signal. One light unit is used to send the data to the user, which is the best light unit. At a receiver side, band pass filters are used to separate subcarrier multiplexing tones. This enables receiver to connect with all light units via subcarrier multiplexing tones. The carrier to noise ratio of each control tone signal is estimated at the receiver, which leads to make the receiver connects with the light unit that offers the best connection during its mobility.